1985
DOI: 10.1159/000275781
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Carbamazepine in the Treatment of Tinnitus

Abstract: A double-blind controlled trial on the use of oral carbamazepine in the treatment of tinnitus is reported. The effects of carbamazepine and intravenous lidocaine on tinnitus were compared. Carbamazepine had less effect than the placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 11 publications
0
18
1
Order By: Relevance
“…Our report has described a distinct tinnitus syndrome responsive to carbamazepine despite well-designed prior studies showing no benefi t of carbamazepine for tinnitus subjects [11][12][13] . The failure of the prior studies to detect this effect is probably due to its infrequent occurrence.…”
Section: Discussioncontrasting
confidence: 58%
“…Our report has described a distinct tinnitus syndrome responsive to carbamazepine despite well-designed prior studies showing no benefi t of carbamazepine for tinnitus subjects [11][12][13] . The failure of the prior studies to detect this effect is probably due to its infrequent occurrence.…”
Section: Discussioncontrasting
confidence: 58%
“…It has been used to treat tinnitus in human patients despite the fact that very few systematic clinical studies have been conducted [2,3,7]. This study is the first to evaluate the efficacy of CBZ in an animal model of tinnitus based on Jastreboff et al's [8] lick-suppression model.…”
Section: Discussionmentioning
confidence: 99%
“…In both of these studies, the side effects from CBZ treatment were mild and transient [2,3]. In contrast, Hulshof and Vermeij [7] reported that CBZ was less effective than a placebo in relieving tinnitus. Despite the use of CBZ in the treatment of tinnitus, these studies represent the majority of the clinical trial data available.…”
Section: Introductionmentioning
confidence: 98%
“…The hypothesis that tinnitus may be a form of 'sensory epilepsy' is the reason that many anti-epileptic drugs, such as carbamazepine, gabapentin and vigabatrin, are often prescribed for the disorder . Nonetheless, the clinical evidence for their efficacy in the treatment of tinnitus is limited (Melding and Goodey, 1979;Hulshof and Vermeij, 1985;Zapp, 2001;Bauer and Brozoski, 2006;Witsell et al, 2007;Bakhshaee et al, 2008) and there remains little consensus about the best drug treatment options for tinnitus.…”
Section: Introductionmentioning
confidence: 99%